Antioxidant, Total Phenolics and Total Flavonoid Content of the Aqueous Extract of Caesalpinia bonducella Seeds - Shruti Shukla (Science Faculty of Chiang Mai University, 2019)
The objective of the present study was to determine the total phenolic and total flavonoid contents, and to evaluate the antioxidant potential of the aqueous extract of Caesalpinia bonducella seeds (AQCB) in various radical scavenging models. The DPPH radical scavenging activity of AQCB (20, 40, 50, 100 and 200 mg/mL) was increased in a dose-dependent manner, which was found in the range of 36.93-70.57% as compared to ascorbic acid (64.26-82.58%) with IC50 values of 86.31 and 26.75 mg/ mL, respectively. The AQCB was also found to scavenge the superoxide generated by EDTA/NBT system. Measurement of total phenolic content of the aqueous extract of C. bonducella was achieved using Folin-Ciocalteau reagent and represented 59.87 mg/g of phenolic content. In addition, flavonoid contents in AQCB were determined to be 22.18 mg quercetin equivalents/g dry mass. The aqueous extract also inhibited the hydroxyl radical, nitric oxide, superoxide anions with IC50 values of 139.95, 114.70 and 83.62 mg/mL, respectively. However, the IC50 values for the standard ascorbic acid were noted to be 71.41, 66.01 and 36.69 mg/mL, respectively. The results obtained in this study indicate that C. bonducella could be considered as a potential source of natural antioxidant with enriched contents of phenolics and flavonoids.